Toxocariasis in Ghanaian neighbourhoods: a need for action - Linda Ama Owusuaa Amoah; Mavis Oppong; Solomon Kofi Amoah; Langbong Bimi (Science in One Health, 2023)
Background: Animal reservoirs of Toxocara spp., a neglected parasitic infection, are frequently found in many Ghanaian neighbourhoods. Despite various interactions occurring between these animals and humans which sustain zoonosis, not much focus has been directed at disease surveillance in Ghana, necessitating this study. Methods: The study was cross-sectional. It combined the collection of biological samples with the survey approach. The study used purposive and convenience sampling techniques to collect data from eligible participants in the Greater Accra region of Ghana. Besides the collection of biological samples from animals which were processed using molecular techniques, semi-structured questionnaires were administered to the pet owners. Results: In sum, 32.2% (95% CI, 27.6%–37.0%) of the targeted animals were positive for Toxocara canis, with most of the cases being found in dogs and rodents. Among the 204 rodents, more Praomys tulbergi were positive for this parasite compared to the others. From the survey, some risk factors culminating in high disease exposure were identified: more than one-third of pet owners did not deworm their pets although about a fourth shared bed with them. In addition, many respondents’ kids played with these pets but not all supervised them to practice hand hygiene. Also, a good number of pet owners confirmed the frequent exposure of their pets to rodents. Conclusions: The relatively high prevalence of T. canis recorded in animals and the increasing exposure of humans to this parasite point to a higher risk for human toxocariasis. Furthermore, T. canis found in cats cannot be ignored and merits further investigations. For Ghana to achieve SDG 3 by 2030, priority must also be placed on neglected diseases which calls for an integrated approach to disease surveillance and a redirection of research focus using the one health concept.